2002
DOI: 10.1161/01.cir.0000041000.94343.28
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a Left Atrial Input to the Atrioventricular Node in Humans

Abstract: Background-During right atrial stimulation, the anterior and posterior approaches provide inputs to the atrioventricular (AV) node. The purpose of the present study was to determine how activation proceeding from the left atrium reaches the AV node. Methods and Results-We studied AV nodal conduction during right and left atrial (coronary sinus) stimulation in 46 patients (27 women and 19 men; mean age, 46Ϯ4 years) who had structurally normal hearts. At an identical cycle length (600 ms), left atrial stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…In all mentioned studies LA stimulation resulted in shorter AH intervals than did RA stimulation. Moreover, Suzuki et al [8] and Gonzalez et al [3] documented (although not consistently) that AVN conduction depends on CS pacing site. Suzuki et al [8] reported that the AH interval was the longest with stimulation from the HRA, followed by the distal, mid, and proximal CS; however, in some patients the AH interval was identical or longer when measured during proximal vs. distal CS pacing.…”
Section: Anterograde Avn Transmission During Pacingmentioning
confidence: 99%
See 4 more Smart Citations
“…In all mentioned studies LA stimulation resulted in shorter AH intervals than did RA stimulation. Moreover, Suzuki et al [8] and Gonzalez et al [3] documented (although not consistently) that AVN conduction depends on CS pacing site. Suzuki et al [8] reported that the AH interval was the longest with stimulation from the HRA, followed by the distal, mid, and proximal CS; however, in some patients the AH interval was identical or longer when measured during proximal vs. distal CS pacing.…”
Section: Anterograde Avn Transmission During Pacingmentioning
confidence: 99%
“…Gonzalez et al [3] found that the AH interval prolonged as the site of pacing was moved from the distal to the proximal CS, but it was always shorter compared with RA stimulation. They explained this finding by a gradual shift between two atrial inputs: from the mitral annulus (MA) that could represent the functional counterpart of the leftward posterior extension to the rightward posterior approach [3].…”
Section: Anterograde Avn Transmission During Pacingmentioning
confidence: 99%
See 3 more Smart Citations